Analisis Kekuatan Tarik Polimer Komposit Polyethylene Terephthalate Berpengisi Karbon Aktif Pada Aplikasi Fuel Cell - Iswandi Iswandi; Djoko Setyanto (CV. IRA PUBLISHING, 2025)
Bipolar plates made from polymer–activated carbon composites offer a lightweight, economical alternative but require a balance between mechanical strength and the amount of carbon filler. This is because a filler fraction that is too high can cause agglomeration and void formation, ultimately reducing the tensile strength and overall performance of the plate. This study aims to evaluate the tensile strength of PET (Polyethene Terephthalate) composites with varying levels of activated carbon. The compositions tested were 90/10, 80/20, and 70/30 (wt%). Specimens were fabricated using a hot press (compression moulding). Tensile testing was conducted in accordance with ASTM D638. The tensile strength value was calculated from the maximum load to the cross-sectional area of ​​the specimen. The test results showed that the composite with 10% activated carbon produced 2.84 MPa. The addition of activated carbon up to 30% decreased the tensile strength to 1.05 MPa. This trend indicates that increasing the activated carbon composition decreases the tensile strength of PET composites for bipolar plate applications.